Dynamic Ambidexterity: Proposal of a Theoretical and Hypothetical Model - Rodrigo Franklin Frogeri; Pedro dos Santos Portugal Júnior; Fabrício Pelloso Piurcosky; Victor Sanacato; Julia López de Calle; Stefano Barra Gazzola; Felipe Flausino de Oliveira (RAC: Revista de Administração Contemporânea, 2021)
Context: ambidexterity is a dynamic capability that seeks to balance exploitation and exploration initiatives. The joint development of exploitation and exploration can be achieved through dynamic ambidexterity. Theoretical discussions involving the relationship between the concepts of ambidexterity and dynamic capabilities (DCs) have already been developed in literature. However, the way the three ambidextrous approaches (structural, contextual, and sequential) are based on DCs still needs to be observed by researchers. Objective: this study aims to propose a conceptual and theoretical hypothetical model that explains the influence of various types of organizational ambidexterity (structural, contextual, and sequential) on the development of DCs and their relation to organizational performance. Methodology: the study was developed through an extensive systematic literature review guided by an inductive logic, interpretive epistemology, and qualitative approach. Results: the analyses and discussions made it possible to present a theoretical hypothetical model of dynamic ambidexterity that involves nine constructs and eleven hypotheses. Conclusion: we believe that our study contributes theoretically to the field of organizational Strategies and can enable studies aligned with the concepts of dynamic ambidexterity and DCs.